2012
DOI: 10.1590/s0037-86822012000500006
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Triatoma costalimai (Hemiptera: Reduviidae) in different environments and climatic seasons: a field study in the Brazilian savanna

Abstract: Introduction: Trypanosoma cruzi-infected specimens of Triatoma costalimai have been detected in domiciliary units of Central Brazil, thereby maintaining the potential risk of vectorial transmission of Chagas disease. The aim of this study was to determine the occurrence and natural infection of T. costalimai in different environments (gallery forest, dry forest and peridomicile) and climatic seasons (wet and dry), in the municipality of Mambaí, State of Goiás, Brazil. Methods: Triatomines were captured in Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
(15 reference statements)
1
16
0
1
Order By: Relevance
“…It is important to note that the DU where the nymphs were collected was located near rock outcroppings, common habitats for this species ( Mello 1981 ). T. costalimai has also been found in the peridomiciliary areas of other municipalities in GO ( Oliveira & Silva 2007 , Machiner et al 2012 ).…”
Section: Discussionmentioning
confidence: 94%
“…It is important to note that the DU where the nymphs were collected was located near rock outcroppings, common habitats for this species ( Mello 1981 ). T. costalimai has also been found in the peridomiciliary areas of other municipalities in GO ( Oliveira & Silva 2007 , Machiner et al 2012 ).…”
Section: Discussionmentioning
confidence: 94%
“…temperature values, rainfall, altitude, vegetation). Although underexplored for Triatominae, the method has given good prediction results, especially on the well sampled species, generating largely coincident predicted and known areas of distribution (Gurgel-Gonçalves et al, 2012;Ibarra-Cerdeña et al, 2009).…”
Section: The Geographic Distribution Of Triatominaementioning
confidence: 99%
“…Collected among calcareous rocks close to nests of mocó (Cavidae) (Lent and Wygodzinsky, 1979;Machiner et al, 2012) Adults found inside human houses and peridomestic structures (Machiner et al, 2012) Yes (Mello and Borges, 1981) T. deaneorum # # Adults found inside human houses (Carcavallo et al, 2001) # #…”
Section: T Carrionimentioning
confidence: 99%
“…The occurrence of this natural infection of T. costalimai by T. cruzi was initially evidenced by Mello and Borges 15 and Mello, 16 in Mambaí -Goiás State (GO), but with infection prevalences of 13.5% and 0.4%, respectively. More recently, also in Mambaí-GO, Machiner et al 17 reported a higher occurrence of T. costalimai in rock outcrops located in the peridomicile, near hens and pigs, comparable to a wild environment, indicating the synanthropic potential of the species, without the presence of T. cruzi infection. In the present study, a similar environment was observed with the high infection prevalence, suggesting the transmission cycle of the parasite among the wild animals that inhabit the rock outcrops where the triatomines were captured.…”
mentioning
confidence: 90%